Konsumsi dan Kemampuan Cerna Pakan pada Kuskus (Spilocuscus maculatus dan Phalanger spp.) - Farida, W. Rosa; Widyastuti, Roi; Sigit, Nuraeni; Khotijah, Lilis (JURNAL BIOLOGI INDONESIA, 2001)
ABSTRACTFeed Consumption and Digestibility Capacity on Cuscuses (Spilocuscus maculatus and Phalanger spp.). The research was conducted to know feed consumption and digestibility capacity on cuscuses in the Small Mammal Captivity on Zoology Division, Research and Developmment Center for Biology, Indonesian Institute of Sciences (LIPI), Bogor. The research material used were five cuscuses, each of them placed in individual cage. Species of cuscuses are Spilocuscus maculatus (two heads), Phalanger orientalis (one), P. gymnotis (one), and P. ornatus (one). The feedstuff is given in fresh form, consists of fruit, leaves, and extra feed. The fruit consists of passion fruit (Passiflora edulis), banana (Musa paradisiaca), guava (Psidium guajava), coconut (Cocos nucifera), and sweet corn (Zea mays). Leaves were kemang (Mangifera caesia), pohpohan (Pilea trinervia), and kangkung (Ipomea aquatica), and sweet potatoes (Ipomea batatas); while extra feed consists of bread and dog food. The result showed that the average of dry matter intake on cuscuses was 37.83 ? 6.94 g DM/kg BW0.75/head/day, while those on S. maculatus was 38.04 ? 6.25 g DM/kg BW0.75/head/day and on Phalanger spp. was 37.68 ? 7.57 g DM/kg BW0.75/day. The digestible coefficient of nutrient on cuscuses was 86.72% dry matter (DM), 66.86% ash, 69.86% crude protein, 95.51% ether extract, 73.58% crude fiber, and 92.09% nitrogen free extract. Total Digestible Nutrient (TDN) on cuscuses was 93.96 ? 3.22% and Digestible energy (DE) was 3.71 ? 0.39 kkal/g DM.Key words : Consumption, digestibility, Spilocuscus maculates, Phalanger spp., captivity